2019
DOI: 10.1177/0961000619880229
|View full text |Cite
|
Sign up to set email alerts
|

Transformational and transactional leadership influence on knowledge management activities of librarians in university libraries in Nigeria

Abstract: This paper aims to determine the influence of transformational and transactional leadership on knowledge management activities of librarians in university libraries in Nigeria. Quantitative methodology was considered appropriate for this type of research and adopted to accomplish the main goal of this study. A questionnaire was used to collect data from a total of 215 librarians who participated in the study. Factor analysis and multiple regressions were used to analyze data. The results of the study reveal a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
(95 reference statements)
1
18
0
1
Order By: Relevance
“…In the context of academia, studies on transactional leadership unveiled questionable findings its role in improving performance. Ugwu and Okore (2020) found a positive effect of transactional leadership on knowledge management. In contrast, Farrukh et al (2019) found that transactional leadership has a negative effect on intrapreneurial behaviour of academic staff of universities in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 96%
“…In the context of academia, studies on transactional leadership unveiled questionable findings its role in improving performance. Ugwu and Okore (2020) found a positive effect of transactional leadership on knowledge management. In contrast, Farrukh et al (2019) found that transactional leadership has a negative effect on intrapreneurial behaviour of academic staff of universities in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Leadership behaviors and characteristics have considerable influences on promoting or restricting a firm's capability of knowledge management. Numerous studies demonstrated the important role of TL in creating a supportive working climate and provides sufficient resources, which are conducive to KMC of an organization (Bass and Avolio, 2000; Choi et al , 2016; Xiao et al , 2017; Le and Lei, 2018; Ugwu and Okore, 2020). For example, Bass and Avolio (2000) supposed that transformational leaders' features (such as charisma, inspirational motivation and intellectual stimulation) positively encourage employees communicating and sharing knowledge with each other.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Regarding the relationship between TL and key elements of KMC, some scholars have demonstrated that TL behaviors are positively related to knowledge acquisition (Crawford, 2005), knowledge preservation and documentation (Nemanich and Vera, 2009), knowledge sharing (Le and Lei, 2018), knowledge creation (Birasnav et al , 2011) and knowledge application (Birasnav, 2013). Recently, Ugwu and Okore (2020) argued that TL is significant associations with some enablers of knowledge management activities such as organizational learning, emerging technologies and reward systems that encourage employees to share knowledge and create new knowledge. Their finding revealed a positive and significant influence of TL on knowledge management activities of academic librarians in university libraries in Nigeria.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Consequently, this enhances the processes of employees' learning to regulate the knowledge flows in organizations (Camps & Rodríguez, 2011). The empirical evidence also displays that leadership affects the regulations of knowledge flows associating with the process of knowledge management such as acquisition, transfer, and application (Ugwu & Okore, 2020). Additionally, leadership affects organizational learning by advocating intellectual stimulation and motivating members' inspiration and self-confidence (Coad & Berry, 1998;García-Morales, Jiménez-Barrionuevo, & Gutiérrez-Gutiérrez, 2012).…”
Section: Research Question 1: How Does Knowledge-oriented Leadership ...mentioning
confidence: 98%